An annotated translation of The Garden of Words by Makoto Shinkai - Muhammad Reza Fardana; Bambang Suryanto; Ririn Pratiwi Suharto (Nautical : Jurnal Ilmiah Multidisiplin Indonesia, 2026)
This study presents an annotated translation of the first two chapters of The Garden of Words (Kotonoha no Niwa) by Makoto Shinkai from English into Indonesian. Employing an introspective-retrospective annotated translation design, this research identifies and analyzes translation problems encountered during the process. A total of 40 problems were identified at the word, phrase, and clause levels, categorized into three types: Understanding (U), Transfer (T), and Understanding & Transfer (U&T), comprising 6, 33, and 1 problem respectively. To resolve these problems, translation strategies proposed by Chesterman (2016) and methods by Newmark (2001) were applied. The semantic strategy was the most frequently utilized (60%), reflecting the predominantly meaning-based nature of the difficulties encountered. Syntactic, pragmatic, idiomatic, literal, free, and recognized translation strategies were additionally employed. The findings indicate that the primary challenge in translating this literary text lies in rendering meaning naturally into the target language rather than in source text comprehension. This study is intended to serve as a practical reference for novice translators working with similar literary texts.